Breast carcinomas associated with microglandular adenosis are linked to germline alterations in homologous recombination-deficiency genes - Christopher J. Schwartz; Iskender Genco; Matteo Repetto; Daniel Muldoon; Andrea Gazzo; Panieh Terraf; Anne Grabenstetter; Dara Ross; Hong Zhang; Diana Mandelker; Simon Powell; Britta Weigelt; et al. (npj Breast Cancer)
Abstract Invasive breast carcinomas associated with microglandular adenosis (IBC-MGA) represent a rare and poorly characterized form of triple-negative breast cancer (TNBC). We analyzed clinical, pathological, and germline genetic data from 38 patients, including 34 IBC-MGAs and 4 in situ cases. Germline pathogenic or likely pathogenic variants in homologous recombination-deficiency (HRD) genes were found in 42% (16/38) of patients, predominantly in BRCA1 (81%, 13/16). Most tumors were grade 3 invasive ductal or metaplastic carcinomas with limited tumor-infiltrating lymphocytes. No significant clinicopathologic differences were observed between germline HRD-associated and sporadic cases. Paired tumor-normal targeted sequencing revealed frequent TP53 mutations and high HRD scores. These findings underscore the relationship of breast carcinomas associated with MGA with HRD-related germline variants and highlight the potential for targeted therapeutic strategies and the importance of genetic testing in this rare subset of TNBC.